(untitled) (Scientia Agropecuaria, 2025)
The expansion of oil palm plantations into peatlands presents a critical area of study, particularly in understanding how nutrient dynamics and groundwater management influence oil palm yield. This research was conducted on smallholder oil palm plantations comprising 8–10-year-old palms cultivated on peat soils in Bengkalis Regency, Riau Province. A completely randomized block design was used, incorporating three groundwater table treatments: A. 40 cm, B. 60 cm, and C. 80 cm. Fertilizer application rates were as follows: urea at 2.50 kg/tree/year, SP-36 at 2.75 kg/tree/year, MOP (KCl) at 2.25 kg/tree/year, and dolomite at 2.00 kg/tree/year. Data analysis utilized a combination of Structural Equation Modeling based on Partial Least Squares (SEM-PLS) and Necessary Condition Analysis (NCA). The results showed that nutrient dynamics, indicated by leaf nutrient content, are the key driver connecting soil nutrient availability with oil palm yield. This finding emphasizes the importance of monitoring and managing nutrient flows through the plant to optimize fertilization strategies and improve yield performance. The combined use of SEM-PLS and NCA provides a robust analytical framework for understanding yield formation and developing nutrient management strategies for oil palm cultivation on peatlands.